Interactive touch-screen monitors facilitate collaborative learning of microscopy skills in an introductory-level plant biology lab. Issue 1 (1st January 2019) - Gould, Kevin S.; Gilbert, Amanda; Pike, Adrian J.; Menzies, Ignatius J.
Abstract: Microscopy skills are critical for many aspects of biology, yet they are notoriously difficult to teach, especially to large classes. We trialled the use of widescreen monitors with touch-screen capability connected to compound microscopes in an introductory-level plant biology lab. Working in teams, students used the screens to interpret, annotate and measure images of their sections taken through fresh leaf material. The lab progressed more rapidly than in previous years in which it was run as a traditional microscopy exercise; it was also far noisier and more congested. Students reported that they valued the size and quality of the images, and the opportunity to work collaboratively to identify the leaf's structural features. All teams expressed a strong appreciation for the group discussions facilitated by the monitors, which presented a safe environment to bounce ideas off one another, and assisted their comprehension. The monitors were seen as an effective and time-efficient tool for collaborative learning of fundamental microscopy skills.